Cytochrome P450 3A Enzymes Are Key Contributors for Hepatic Metabolism of Bufotalin, a Natural Constitute in Chinese Medicine Chansu - Dai, Zi-Ru; Ning, Jing; Sun, Gui-Bo; Wang, Ping; Zhang, Feng; Ma, Hong-Ying; Zou, Li-Wei; Hou, Jie; Wu, Jing-Jing; Ge, Guang-Bo; Sun, Xiao-Bo; Yang, Ling (Frontiers in Pharmacology, 2019)
Bufotalin (BFT), one of the naturally occurring bufodienolides, has multiple pharmacological and toxicological effects including antitumor activity and cardiotoxicity. This study aimed to character the metabolic pathway(s) of BFT and to identify the key drug metabolizing enzyme(s) responsible for hepatic metabolism of BFT in human, as well as to explore the related molecular mechanism of enzymatic selectivity. The major metabolite of BFT in human liver microsomes (HLMs) was fully identified as 5β-hydroxylbufotalin by LC-MS/MS and NMR techniques. Reaction phenotyping and chemical inhibition assays showed that CYP3A4 and CYP3A5 were key enzymes responsible for BFT 5β-hydroxylation. Kinetic analyses demonstrated that BFT 5β-hydroxylation in both HLMs and human CYP3A4 followed the biphasic kinetics, while BFT 5β-hydroxylation in CYP3A5 followed substrate inhibition kinetics. Furthermore, molecular docking simulations showed that BFT could bind on two different ligand-binding sites on both CYP3A4 and CYP3A5, which partially explained the different kinetic behaviors of BFT in CYP3A4 and CYP3A5. These findings are very helpful for elucidating the phase I metabolism of BFT in human and for deeper understanding the key interactions between CYP3A enzymes and bufadienolides, as well as for the development of bufadienolide-type drugs with improved pharmacokinetic and safety profiles..